2019
DOI: 10.20964/2019.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hazardous Bacteria Isolated From Copper Plumbing System on Microbiologically Influenced Corrosion of Copper

Abstract: Plumbing systems can be affected by Microbiologically Induced Corrosion (MIC). Through this process, microorganisms can modify water quality and jeopardize consumers' health by releasing metal from pipes' surface into the water. While it is known that microorganisms' interactions increase their electrochemical effect on the metal surface, the effect of mixed communities and their interactions remain poorly understood. In this work, we investigated two hazardous bacteria isolated from a copper plumbing system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The development of a heterogeneous biofilm likely enhanced the weak oxide layer with low protective capacity. Previous research revealed that the presence of a consortium of microorganisms with the ability for biofilm production promotes the precipitation of copper hydroxide with low protective function in comparison with the abiotic condition [42]. This situation and regular replacement of water in the copper pipes every 8 h might explain the low coverage of corrosion byproducts on the pipes exposed for 3 and 12 months.…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a heterogeneous biofilm likely enhanced the weak oxide layer with low protective capacity. Previous research revealed that the presence of a consortium of microorganisms with the ability for biofilm production promotes the precipitation of copper hydroxide with low protective function in comparison with the abiotic condition [42]. This situation and regular replacement of water in the copper pipes every 8 h might explain the low coverage of corrosion byproducts on the pipes exposed for 3 and 12 months.…”
Section: Water Qualitymentioning
confidence: 99%
“…The presence of sulfate, bicarbonate, and orthophosphate enhances the formation of brochantite and cupric phosphate during long periods, which would prevent the formation of insoluble tenorite or malachite phases [43] from creating a weak oxide layer. Moreover, previous research indicates that the presence of a biofilm creates an acidic microenvironment that hastens the formation of soluble copper compounds as cupric hydroxide (Cu(OH) 2(s) ) [7,25,42,44].…”
Section: Flushing Experimentsmentioning
confidence: 99%
“…Microorganisms, exhibiting a high level of diversity and adaptability, are prevalent in natural and industrial environments. They are capable of causing corrosion in almost all types of metals and alloys ( Galarce et al, 2019 ; Gu et al, 2019 ). The operating environment that condensing systems provide is conducive to the growth and reproduction of microorganisms ( Aruliah and Ting, 2014 ).…”
Section: Introductionmentioning
confidence: 99%